P224 Lymph Node Assessment In Surgical Resection Of Non-small Cell Lung Cancer (nsclc): Are We Hitting The Target?. (10th November 2014) - McKay, AC; Ewan, H; Beattie, G; Kirk, AJB; Asif, M
Abstract : Introduction: Guidelines from the British Thoracic Society (BTS) and the National Institute for Health and Care Excellence (NICE) recommend that nodal assessment be performed in all patients who have anatomical lung resection for NSCLC. Nodal status is one of the major determinants of outcome and most multidisciplinary teams now record adequacy of nodal assessment. N1 nodes are removed with the specimen perforce; therefore, a better indicator of surgical performance is the number of N2 nodal stations sampled. This paper describes a continual audit cycle of lymph node sampling performance data in relation to N2 nodes. Methods: A retrospective analysis of patients who underwent anatomical lung resection for NSCLC in the calendar years 2009, 2010, 2012 and 2013 was undertaken. Lymph node sampling data was taken from pathology reports. The number of different stations sampled, rather than number of individual lymph nodes, was counted. Basic patient demographics were also collected. After each audit cycle individual results were tracked and presented at open local, regional and national forums. Results: A total of 937 patients were audited after anatomic lung resection for NSCLC during the study periods. Pathology of NSCLC resections were as follows: 52% adenocarcinoma, 33.9% squamous cell carcinoma, 7.3% large cell carcinoma, 6.1% other. The data is summarised in the table below: Conclusion: Audit over the past 3 years shown steady improvement in lymph node assessment performance. Continuous auditing and presentation of individual surgeon data at local, regional and national forums has contributed to the increasing compliance to the guideline targets There remains scope for further improvement and consultant engagement. Re-auditing will be essential to further improve compliance with guidelines.